MOTIVATIONAL STRATEGIES IN THE CLASSROOM APPLIED BY TWO ENGLISH LECTURERS OF IAIN PALANGKA RAYA - Adawiyah, Rabiatul; Asi, Natalina; Luardini, Maria Arina (Journal Compound: Improving the Quality of English Education, 2019)
This research was aimed to identify the implementation of the motivational strategies in the classroom performed by two English lecturers of IAIN Palangka Raya and to describe the learners? motivated behaviors in the classroom as the response to the motivational strategies based on Dornyei (2001). This research was a case study in descriptive qualitative research design. The subjects of the research were two English lecturers of IAIN Palangka Raya and their learners. The researcher as the main instrument of the research used observation, interview, and documentation to collect the data. The research findings showed some points as follows: First, two English lecturers of IAIN Palangka Raya applied four aspects of motivational strategies. They were creating the basic motivational conditions, generating initial motivation, maintaining and protecting motivation, and then encouraging positive retrospective self-evaluation. The lecturers applied the same motivational strategies in various ways. They applied 29 strategies of 35 motivational strategies by Dornyei (2001). Second, the learners? motivated behaviors at each lecturer?s classroom were different in the aspect of participation. At lecturer A class, the learners? motivated behaviors appeared in the learning process were that they had high attention, high participation, and eager volunteering to lecturer-fronted activity. While at lecturer B class, the learners had high attention, low participation, and eager volunteering to lecturer-fronted activity.